2019
DOI: 10.5539/jas.v11n2p541
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic Acid Utilization in Seeds and Plants of Beans: Effect on Growth and Seeds Physiological Quality

Abstract: The growth regulators from gibberellins, when applied on plants, might improve physic and physiological features, stimulate cell division and elongation, this study aimed at evaluating the influence of gibberellic acid doses applied exogenously on bean crop through seed treatment, and analyzing its effects on morphological attributes of seedlings and physiological quality of the seeds produced. The experimental design was completely randomized design, with treatments corresponding to the doses: zero (distilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The root dry weight was always higher in BARI Mung-8 than in BARI Mung-6 in this study. It has been reported that GA 3 increases the root dry weight in beans (Jaques et al, 2019), Trigonella foenumgraecum (Ahmad Dar et al, 2015), the dry weight of pods in French bean (Gabal et al, 1990), and bulbs in onion (Hore et al, 1988). However, exogenous application of GA 3 through seed priming in V. radiata did not influence the root dry weight as reported by Kundu et al (2017), which contradicts in our findings.…”
Section: Root Dry Weightmentioning
confidence: 99%
“…The root dry weight was always higher in BARI Mung-8 than in BARI Mung-6 in this study. It has been reported that GA 3 increases the root dry weight in beans (Jaques et al, 2019), Trigonella foenumgraecum (Ahmad Dar et al, 2015), the dry weight of pods in French bean (Gabal et al, 1990), and bulbs in onion (Hore et al, 1988). However, exogenous application of GA 3 through seed priming in V. radiata did not influence the root dry weight as reported by Kundu et al (2017), which contradicts in our findings.…”
Section: Root Dry Weightmentioning
confidence: 99%
“…They offer high protein and amino acid content while being lower in calories and saturated fat than many high protein sources, such as meat and dairy products [5]. The regulators may be composed of indolebutyric acid, kinetin and gibberellic acid, which act to increase plant growth and development, increase cell wall extensibility, and absorb water and nutrients [6]. Gibberellins constitute a group of plant hormones that act in the elongation and cell division [7], which are synthesized in the form of gibberellic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellins constitute a group of plant hormones that act in the elongation and cell division [7], which are synthesized in the form of gibberellic acid. This regulator's concentration and plant tissues sensitiveness to this compound determine plants response regarding growth and development Thus, the exogenous application of gibberellic acid in bean plants may directly influence plant growth, as well as its morphological and reserve attributes [5,6]. This study aimed at evaluating the influence of gibberellic acid applied exogenously on bean crop due to growth, and analyzing its effects on morphological attributes of physiological quality of the seeds produced.…”
Section: Introductionmentioning
confidence: 99%